2012
DOI: 10.4236/ce.2012.326112
|View full text |Cite
|
Sign up to set email alerts
|

Delivering Creative Education for Health Promoters in Africa–Towards Critical Mass by “Going Global and Staying Local”

Abstract: Postgraduate opportunities for health promotion and other courses allied to health are limited in sub-Saharan Africa (apart from South Africa). There are major constraints on the development of health promotion in sub-Saharan Africa, and the lack of training capacity is one of them. Although potential students can access courses in parts of the global North where health promotion is strong – Europe, North America, Australia – this option is expensive. It also takes workers away from their posts for considerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…They found that high-activity involvement led to high-identity salience to the Basketball events (Laverie and Arnett, 2000). Other studies have demonstrated how events can lead to a sense of group identity and place identity (De Bres and Davis, 2001; 212 IJEFM 5,3 Dixey, 2012), yet the complexity of how respondents develop their identity has not been undertaken in-depth. Within this study, the participants in the Adelaide Fringe Festival appear to be involved in activities which are linked to the content of the festival, and therefore it is indicated that their involvement begins outside of the event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that high-activity involvement led to high-identity salience to the Basketball events (Laverie and Arnett, 2000). Other studies have demonstrated how events can lead to a sense of group identity and place identity (De Bres and Davis, 2001; 212 IJEFM 5,3 Dixey, 2012), yet the complexity of how respondents develop their identity has not been undertaken in-depth. Within this study, the participants in the Adelaide Fringe Festival appear to be involved in activities which are linked to the content of the festival, and therefore it is indicated that their involvement begins outside of the event.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Jaeger and Mykeltun (2012) adopted a qualitative method to explore how four events in Finnmark, Norway contribute to a sense of belonging and place identity. Qualitative data from this study identified themes relating to place identity and demonstrated that the events offer opportunities for residents to share experiences and build collective images and values of the place (Dixey, 2012). In addition to these event specific studies, the leisure and recreational literature offer concepts which can be applied within an events context.…”
Section: Social Impactmentioning
confidence: 96%
“…Reference is also made to the need to equip student for their future 'as citizens in an increasingly interdependent/globalising world' (Killick, 2008: 2). Fielden (2011: 8) draws a distinction between internationalisation abroad, involving staff and students moving in and out of the United Kingdom, and internationalisation at home, concerning the internationalisation of the curriculum and enhancing the quality of the international student experience, raising the question as to the extent it is possible to 'think globally' while 'staying local' (Dixey, 2012). The partnership described in this article falls within the broader concept of internationalisation in higher education whereby the involvement of staff in an international project has the potential to contribute to the internationalisation of the curriculum in the United Kingdom, as well as in Zambia.…”
Section: The International Agenda In Higher Education and Social Workmentioning
confidence: 99%